Comparison of sorghum [Sorghum bicolor. (L) Moench] genotypes in Indo-gangetic plain of Prayagraj, U.P - Murari Mohan; Umesha C; Vaidurya Pratap Sahi; Prashant Kumar Rai; Satyam Ranjan; Priyanka Priya (Annals of Agricultural Research, 2024)
A field experiment was conducted during Kharif season, 2023 to study the “Comparison of Sorghum (Sorghum bicolor L. Moench) genotypes grown in Indo-Gangetic plain of Prayagraj, U.P’’ at SHUATS, Department of Agronomy, Naini Agricultural Institute, Prayagraj (U.P). The soil was sandy loam in texture, moderately acid in reaction (pH 5.8), medium in available N (249.50 kg/ha), medium in available phosphorus (24.2 kg/ha), available potassium (220.6 kg/ha) and organic carbon (0.422 %). The treatment consists of three different Genotypes and each genotype is divided into four sub genotypes. The experiment was laid out in a randomized block design with 12 treatments replicated thrice. The results showed that significantly highest growth attributes of Sorghum at 100 DAS have increased the growth parameters viz., Plant height (360.00 cm), Plant dry matter accumulation (239.99 g), Number of leaves/ plant (15.67), was observed in treatment - 7 genotype i.e. PC - 6 (ICSH-101105) and significantly increased the growth attributing parameters viz., Number of internodes/plant (17.81), Brix % (11.17) was observed in treatment - 4, Genotypes, SSV -74, (ICSH- 100791).